Transport energy consumption of rural households in the Tibetan Plateau of China. Issue 3 (19th August 2021) - Li, Hongqing; Xing, Ran; Jiang, Lu; Li, Chunhua; Xue, Bing
Abstract : Transportation has become the world's second-largest energy-consuming sector, yet existing works mainly focus on the macro perspective and the causal relationships with social–economic–environment dimensions, leaving a significant knowledge gap at the household or individual level. Studying household-scale transport energy structure research is of great significance for exploring the driving mechanism of carbon dioxide emissions and promoting sustainable development. This study focuses on the region of the Tibetan Plateau of China. Field-based surveys and semi-structured interviews were conducted to investigate the transport energy consumption of rural households from the perspectives of sub-region (agricultural area, pastoral area, agropastoral area) and income (low-income, lower-middle-income, middle-income, upper-middle-income and high-income). On the basis of 498 samples, detailed energy consumption structures and environmental factors are presented. The authors hope that in the future, there will be more reports on household transport energy in different regions to provide a scientific basis for understanding and promoting household energy transition.